Electrochemical device and electronic device
By selecting specific positive electrode active material particles in the positive electrode material layer of the lithium-ion battery to ensure their morphological characteristics and interlaced distribution, the problem of insufficient rate performance of lithium-ion batteries at low temperatures and room temperatures is solved, and more efficient lithium-ion transmission and electrochemical performance improvements are achieved.
Patent Information
- Application Number
- CN202180046458.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-12-15
AI Technical Summary
The rate performance of the positive electrode active materials of existing lithium-ion batteries is insufficient at low temperatures and room temperatures, which affects the overall performance of the electrochemical device.
By selecting specific cathode active material particles in the cathode material layer, the ratio of the minimum circumferential circle radius of its profile to the maximum inscribed circle radius is between 1 and 3, ensuring the staggered distribution of particles after the compaction process, improving the lithium ion embedding and deintercalation kinetics of the material.
It improves the transmission efficiency of lithium ions and significantly improves the rate performance of electrochemical devices at low temperatures and room temperatures.
Smart Images

Figure CN115956306B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to an electrochemical device and an electronic device. Background Art
[0002] Lithium-ion batteries are widely used in wearable devices, smart phones, drones, electric vehicles and large energy storage equipment due to their high energy density, long cycle life and no memory effect. They have become the new green chemical power source with the greatest development potential in the world today. However, with the widespread application of lithium-ion batteries, the market has put forward higher requirements on the comprehensive performance of lithium-ion batteries.
[0003] The positive electrode active material, negative electrode active material and electrolyte in lithium-ion batteries are important parameters that affect the performance of lithium-ion batteries. Among them, the selection of positive electrode active materials will affect the transmission efficiency of lithium ions, thereby affecting the electrochemical performance of electrochemical devices, such as rate performance. However, the existing positive electrode active materials need to be further optimized to improve the rate performance of electrochemical devices. Summary of the invention
[0004] The purpose of the present application is to provide an electrochemical device and an electronic device to improve the rate performance of the electrochemical device at low temperature and room temperature.
[0005] The first aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and in a scanning electron microscope photograph of a cross section of the positive electrode material layer, an area greater than 5 μm 2 The radius of the minimum circumscribed circle of the contour of the positive electrode active material particle is R c , area larger than 5μm 2 The radius of the maximum inscribed circle of the contour of the positive electrode active material particle is R i , satisfying 1<R c / R i The average value of is ≤3. For example, R c / R i The average value of can be 1.1, 1.5, 1.8, 2, 2.3, 2.5, 2.8, 3 or any range therebetween. Without being limited to any theory, the electrochemical device provided by the present application, wherein the positive electrode active material in the positive electrode material layer satisfies 1<R c / R i The average value of is ≤3, which can effectively improve the transmission efficiency of lithium ions during the charging and discharging process, thereby improving the rate performance of the electrochemical device at room temperature and low temperature (for example, temperature less than or equal to 0°C). This may be due to the fact that R c / R iThe positive electrode material layer whose average value is within the above range has a morphology that enables the positive electrode active material to maintain a stable crystal structure in a large rate cycle, and effectively improves the lithium ion insertion and deinsertion kinetics of the positive electrode active material, provides good lithium ion transport performance, and thus improves the rate performance of the electrochemical device. In this application, the cross section of the positive electrode material layer refers to the cross section obtained along the thickness direction of the positive electrode material layer.
[0006] In some embodiments of the present application, the area is greater than 5 μm 2 The positive electrode active material particles include a first particle and a second particle, and the radius of the minimum circumscribed circle of the contour of the first particle is R c1 , the radius of the maximum inscribed circle of the first particle's outline is R i1 , satisfying 1<R c1 / R i1 The average value of is ≤1.5; the radius of the minimum circumscribed circle of the contour of the second particle is R c2 , the radius of the maximum inscribed circle of the second particle's outline is R i2 , satisfying 1.5<R c2 / R i2 The average value is ≤3.
[0007] Based on the cross-sectional area of the positive electrode material layer, the area percentage of the first particles is greater than 0% and less than or equal to 50%, and the area percentage B of the second particles is 30% to 80%. c1 / R i1 The average value of can be 1.1, 1.2, 1.3, 1.4, 1.5 or any range therebetween; c2 / R i2 The average value of can be 1.6, 2, 2.5, 3 or any range therebetween; the area percentage of the first particles can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any range therebetween; the area percentage B of the second particles can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any range therebetween.
[0008] The first particles and the second particles are distributed in the positive electrode material layer in the above ratio, and after the compaction process, different R c / R iThe staggered distribution between particles with a value improves the distribution network of the positive electrode active material and the conductive agent, thereby effectively reducing the interface side reactions in the positive electrode material layer, improving the lithium ion transmission efficiency and the internal electronic conductivity of the positive electrode sheet, and achieving effective improvement of the rate performance and cycle performance of the electrochemical device. When the area percentage B of the second particle is too small (for example, less than 30%), the area percentage of the first particle is too large, the compaction density of the positive electrode sheet is reduced, and the transmission efficiency of lithium ions is affected; when the area percentage B of the second particle is too large (for example, greater than 80%), it will also cause the compaction density of the positive electrode sheet to decrease, affecting the transmission efficiency of lithium ions, thereby affecting the rate performance of the electrochemical device at room temperature and low temperature. By regulating the area percentage of the first particle and the area percentage of the second particle within the scope of this application, it is beneficial to improve the rate performance of the electrochemical device at room temperature and low temperature. In this application, the compaction density of the positive electrode sheet refers to the compaction density of the positive electrode material layer in the positive electrode sheet.
[0009] In some embodiments of the present application, the average cross-sectional area of the first particles is smaller than the average cross-sectional area of the second particles, which is beneficial for reducing the lithium ion transmission path and improving the rate performance of the electrochemical device.
[0010] In some embodiments of the present application, the electrochemical device satisfies at least one of the conditions (a) to (b): (a) the positive electrode active material includes lithium manganate; the lithium manganate includes doped lithium manganate and / or lithium manganate containing a coating layer. The present application has no particular restrictions on the doping elements in the doped lithium manganate, as long as the purpose of the present application can be achieved. For example, the doping elements may include but are not limited to at least one of Al, Nb, Mg, Ti, F, B, Zr, W, Sr, Y, Ce or La. The present application has no particular restrictions on the elements in the coating layer of the lithium manganate containing a coating layer, as long as the purpose of the present application can be achieved. For example, the elements in the coating layer may include but are not limited to at least one of Al, Sr, Zr, Ti or B. (b) The positive electrode active material includes a composite metal oxide of lithium element and a transition metal element, the transition metal element includes Mn and a metal element M1, and the metal element M1 includes at least one of Ni, Co or Fe. Based on the mass of the positive electrode active material, the mass percentage of Mn is 30% to 65%, and the mass percentage of the metal element M1 is 2% to 25%. When the electrochemical device satisfies at least one of the conditions (a) to (b), it is beneficial to improve the cycle performance and low-temperature rate performance of the electrochemical device.
[0011] In some embodiments of the present application, the second particles include a metal element M2, and the metal element M2 includes at least one of Al, Mg, or Nb.
[0012] In some embodiments of the present application, based on the mass of the second particle, the mass percentage of the metal element M2 is 0.1% to 3%. For example, the mass percentage of the metal element M2 can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.5%, 3% or any range therebetween.
[0013] In the related art, manganese-containing positive electrode active materials (such as lithium manganate) are widely used in electrochemical devices, such as lithium ion batteries. 3+ It is easy to undergo disproportionation reaction, resulting in manganese (Mn 2+ ) is dissolved, and then migrates to the negative electrode through the electrolyte, destroying the solid electrolyte interface (SEI) film of the negative electrode. Repairing the SEI film will cause active lithium loss, thereby affecting the cycle performance and rate performance of the lithium-ion battery. In this application, the negative electrode may refer to the negative electrode sheet.
[0014] The inventors of the present application have discovered that, for an electrochemical device comprising a manganese-containing positive electrode active material, when the positive electrode active material comprises a metal element M1, by selecting the above-mentioned metal element M1, it is beneficial to improve the manganese dissolution phenomenon, thereby reducing the damage to the negative electrode SEI film, and repairing the loss of active lithium caused by the consumption of lithium by the SEI film, thereby improving the cycle performance and rate performance of the electrochemical device.
[0015] The inventors of the present application have discovered that when the second particles include a metal element M2, by selecting the above-mentioned metal element M2, the interfacial side reactions between the second particles and the electrolyte during low-temperature charging and discharging can be reduced, thereby improving the internal resistance of the positive electrode sheet and enhancing the low-temperature rate performance of the electrochemical device.
[0016] The inventors of the present application have discovered that when the mass percentage of the metal element M2 is too low (for example, less than 0.1%), the improvement of the side reaction between the second particle and the electrolyte is not obvious. When the mass percentage of the metal element M2 is too high (for example, greater than 3%), it is impossible to further improve the side reaction between the second particle and the electrolyte, and the gram capacity of the positive electrode active material will be reduced. By regulating the mass percentage of the metal element M2 within the above range, it is beneficial to reduce the interfacial side reactions between the second particles and the electrolyte and improve the cycle performance of the electrochemical device. In the present application, the negative electrode may refer to the negative electrode sheet.
[0017] In some embodiments of the present application, the volume particle size distribution of the positive electrode active material satisfies at least one of the conditions (c) to (d): (c) 9 μm ≤ Dv50 ≤ 22 μm; (d) 0.9 ≤ (Dv90-Dv10) / Dv50 ≤ 2. For example, the Dv50 of the positive electrode active material may be 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, or any range therebetween. For example, the value of (Dv90-Dv10) / Dv50 may be 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, or any range therebetween. By regulating the volume particle size distribution of the positive electrode active material to meet at least one of conditions (c) to (d), it is beneficial to improve the rate performance of the electrochemical device at room temperature and low temperature. The present application has no special restrictions on the Dv90 and Dv10 of the positive electrode active material, as long as the value of (Dv90-Dv10) / Dv50 is within the above range. For example, the Dv90 of the positive electrode active material is 15μm to 40μm, and the Dv10 of the positive electrode active material is 0.5μm to 6μm. Among them, the value of (Dv90-Dv10) / Dv50 mainly reflects the particle size distribution of the positive electrode active material.
[0018] In some embodiments of the present application, the electrochemical device further comprises an electrolyte, the electrolyte comprising a linear carbonate and a cyclic carbonate, based on the mass of the electrolyte, the mass percentage of the linear carbonate is ω1, the mass percentage of the cyclic carbonate ω2 is 25% to 50%, and ω1 / ω2 is 0.75 to 2.5. For example, the mass percentage of the cyclic carbonate ω2 can be 25%, 30%, 35%, 40%, 45%, 50% or any range therebetween; the value of ω1 / ω2 can be 0.75, 1, 1.25, 1.5, 1.75, 2, 2.25, 2.5 or any range therebetween.
[0019] Without being limited to any theory, in regulating the R c / R i At the same time, the electrolyte includes chain carbonates and cyclic carbonates, which produce a synergistic effect between the positive electrode active material and the electrolyte, can improve the lithium ion transmission path, especially improve the lithium ion transmission efficiency at the interface between the positive electrode active material and the electrolyte, thereby improving the rate performance of the electrochemical device.
[0020] Without being limited to any theory, when the mass percentage of cyclic carbonate ω2 is too low (for example, less than 25%), the cyclic carbonate cannot form a good synergistic effect with the chain carbonate to improve the transmission efficiency of lithium ions; when the mass percentage of cyclic carbonate ω2 is too high (for example, greater than 50%), the viscosity of the electrolyte increases, which is not conducive to the transmission of lithium ions, thereby affecting the rate performance of the electrochemical device. When the value of ω1 / ω2 is less than 0.75 or greater than 2.5, it will affect the synergistic effect between the cyclic carbonate and the chain carbonate, thereby affecting the transmission efficiency of lithium ions. By regulating the mass percentage of cyclic carbonate ω2 and the value of ω1 / ω2 within the scope of this application, the positive electrode active material can be fully infiltrated, thereby improving the transmission efficiency of lithium ions at the interface between the positive electrode active material and the electrolyte, thereby improving the rate performance of the electrochemical device.
[0021] In some embodiments of the present application, 35%≤ω1≤65%. For example, the mass percentage content of the linear carbonate ω1 can be 35%, 40%, 45%, 50%, 55%, 60%, 65% or any range therebetween. Without being limited to any theory, by regulating the mass percentage content ω1 of the linear carbonate within the scope of the present application, it is beneficial to form a good synergistic effect between the cyclic carbonate and the linear carbonate, improve the transmission efficiency of lithium ions, and thus improve the rate performance of the electrochemical device.
[0022] In some embodiments of the present application, the linear carbonate includes at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethyl propyl carbonate (EPC), dipropyl carbonate (DPC), methyl isopropyl carbonate, methyl butyl carbonate or dibutyl carbonate (DBC). Without being limited to any theory, by selecting the above-mentioned linear carbonate, it is beneficial to improve the transmission efficiency of lithium ions and improve the rate performance of the electrochemical device.
[0023] In some embodiments of the present application, the cyclic carbonate includes at least one of ethylene carbonate (EC), propylene carbonate (PC) or butylene carbonate (BC). Without being limited to any theory, by selecting the above cyclic carbonate, it is beneficial to improve the transmission efficiency of lithium ions and improve the rate performance of the electrochemical device.
[0024] In some embodiments of the present application, the electrolyte includes a sulfonate compound, and the mass percentage of the sulfonate compound is A based on the mass of the electrolyte, satisfying 0.006≤A / B≤0.1. For example, the value of A / B can be 0.006, 0.008, 0.01, 0.02, 0.04, 0.06, 0.08, 0.1 or any range therebetween. Without being limited to any theory, the sulfur-oxygen double bond in the sulfonate compound is beneficial to improving the stability of the SEI film, reducing the deposition of dissolved manganese at the negative electrode, thereby improving the cycle performance of the electrochemical device. At the same time, when the value of A / B is within the scope of the present application, it is beneficial to produce a synergistic effect between the sulfonate compound and the positive electrode active material, while improving the stability of the SEI film, improving the transmission efficiency of lithium ions, and further improving the rate performance of the electrochemical device.
[0025] In some embodiments of the present application, 0.5% ≤ A ≤ 10%. For example, the mass percentage A of the sulfonate compound can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any range therebetween. Without being limited to any theory, when the mass percentage A of the sulfonate compound is too low (e.g., less than 0.5%), the improvement of the stability of the SEI film is not obvious; when the mass percentage A of the sulfonate compound is too high (e.g., greater than 10%), an overly thick or overly dense SEI film will be formed, which will hinder the transmission of lithium ions and cause the rate performance of the electrochemical device to decrease.
[0026] Preferably, the sulfonate compound includes at least one of the following structural compounds I-1 to I-14. The selection of the sulfonate compound with the following structure is beneficial to improving the stability of the SEI film, reducing the deposition of dissolved manganese at the negative electrode, and thus improving the cycle performance of the electrochemical device.
[0027]
[0028]
[0029] In some embodiments of the present application, the electrochemical device further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode material layer, the negative electrode material layer comprises a negative electrode active material, and the negative electrode active material comprises at least one of artificial graphite, natural graphite or hard carbon. Without being limited to any theory, by selecting the above-mentioned negative electrode active material, it is more conducive to forming a synergistic effect with the above-mentioned positive electrode active material and / or electrolyte to improve the cycle performance and rate performance of the electrochemical device.
[0030] In the present application, the positive electrode active material may include but is not limited to at least one of a composite oxide and / or a sulfide, selenide or halide of the composite oxide. The composite oxide may include but is not limited to LiMn2O4, Li(Ni a1 Cob1 Mn c1 )O2 (0 < a1 < 1, 0 < b1 < 1, 0 < c1 < 1, a1 + b1 + c1 = 1), LiNi 1-y1 Co y1 O2 (0 < y1 < 1), LiNi 2- y3 Mn y3 O4 (0 < y3 < 2), Li(Ni a3 Co b3 Al c3 )O2 (0 < a3 < 1, 0 < b3 < 1, 0 < c3 < 1, a3 + b3 + c3 = 1) or LiMn p Fe q PO4 (0 < p < 1, 0 < q < 1, p + q = 1) or at least one of LiFePO4.
[0031] Optionally, an amorphous compound or a crystalline compound may also be present on the surface of the composite oxide. The amorphous or crystalline compound may include, but is not limited to, at least one of an oxide of element Z, a hydroxide of element Z, a hydroxyoxide of element Z, a carbonate oxide of element Z, or a basic carbonate of element Z. Among them, element Z may include, but is not limited to, at least one of Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, or Zr.
[0032] The present application does not particularly limit the preparation method of the composite oxide having an amorphous compound or a crystalline compound on the surface, as long as the object of the present application can be achieved, such as a spraying method or an impregnation method, etc.
[0033] In the present application, the positive electrode material layer may further include a conductive agent. The present application does not particularly limit the conductive agent, as long as the object of the present application can be achieved. For example, it may include, but is not limited to, at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, Ketjen black, graphene, metal materials, or conductive polymers. The above carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above carbon fibers may include, but are not limited to, vapor-grown carbon fibers (VGCF) and / or nanofibers. The above metal materials may include, but are not limited to, metal powders and / or metal fibers. Specifically, the metal may include, but is not limited to, at least one of copper, nickel, aluminum, or silver. The above conductive polymers may include, but are not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, or polypyrrole. In the present application, based on the mass of the positive electrode material layer, the mass percentage content of the conductive agent is 0.5% to 5%.
[0034] In the present application, the positive electrode material layer may also include a positive electrode binder. The present application has no particular limitation on the positive electrode binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon.
[0035] In the present application, the positive electrode sheet includes a positive current collector. There is no particular restriction on the positive current collector, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to aluminum foil, aluminum alloy foil or composite current collector, etc. In the present application, there is no particular restriction on the thickness of the positive current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 8 μm to 20 μm.
[0036] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive current collector and the positive electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, for example, including but not limited to the above conductive agent and the above positive electrode binder.
[0037] In the present application, the negative electrode material layer may further include a conductive agent. The present application has no particular limitation on the conductive agent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above conductive agents.
[0038] In the present application, the negative electrode material layer may also include a negative electrode binder. The present application has no particular limitation on the negative electrode binder as long as the purpose of the present application can be achieved. For example, it may include but is not limited to difluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or at least one of nylon.
[0039] In the present application, the negative electrode sheet includes a negative electrode current collector. Among them, the negative electrode current collector is not particularly limited, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or composite current collector, etc. In the present application, there is no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm.
[0040] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art, and may include but is not limited to the above-mentioned conductive agent and the above-mentioned negative electrode binder.
[0041] In the present application, the electrolyte may also include a non-aqueous solvent. The present application has no particular restrictions on the non-aqueous solvent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of a carboxylic acid ester compound, an ether compound or other organic solvents. The above-mentioned carboxylic acid ester compound may include but is not limited to methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, γ-butyrolactone, 2,2-difluoroethyl acetate, valerolactone, butyrolactone, ethyl 2-fluoroacetate, ethyl 2,2-difluoroacetate, ethyl trifluoroacetate, ethyl 2,2,3,3,3-pentafluoropropionate, 2,2,3,3,3-pentafluoropropionate, ethyl ... At least one of 4,4,4,4-heptafluorobutyrate, 4,4,4-trifluoro-3-(trifluoromethyl)butyrate, 2,2,3,3,4,4,5,5,5,5-nonafluoropentanoate, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9,9-heptafluorononanoate or 2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9,9-heptafluorononanoate. The above-mentioned ether compound may include but is not limited to at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dibutyl ether, tetrahydrofuran, 2-methyltetrahydrofuran or bis(2,2,2-trifluoroethyl) ether. The above-mentioned other organic solvents may include, but are not limited to, at least one of ethyl vinyl sulfone, methyl isopropyl sulfone, isopropyl sec-butyl sulfone, dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester.
[0042] In the present application, the electrolyte may also include a lithium salt. The present application has no particular limitation on the lithium salt as long as the purpose of the present application can be achieved. For example, it may include but is not limited to lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiB(C2O4)2), lithium difluorooxalatoborate (LiBF2(C2O4)), lithium hexafluoroantimonate (LiSbF6), lithium perfluorobutylsulfonate (LiC4F9SO3), lithium perchlorate (LiClO4), lithium aluminate (LiAlO2), lithium tetrachloroaluminate (LiAlCl4), lithium bis(C2O4)2, and lithium bis(C2O4)2. x F 2x+1 SO2)(C y F2y+1 SO2), wherein x and y are natural numbers less than or equal to 4, respectively), at least one of lithium chloride (LiCl) and lithium fluoride (LiF). Preferably, the lithium salt includes LiPF6. The present application has no particular limitation on the concentration of the lithium salt, as long as the purpose of the present application can be achieved, for example, the concentration is 0.5 mol / L to 3 mol / L, preferably 0.5 mol / L to 2 mol / L, and more preferably 0.6 mol / L to 1.5 mol / L.
[0043] The electrochemical device of the present application also includes an isolating membrane. The present application has no special restrictions on the isolating membrane, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO) isolating membranes, polyester membranes (such as polyethylene terephthalate (PET) membranes), cellulose membranes, polyimide membranes (PI), polyamide membranes (PA), spandex, aramid membranes, woven membranes, non-woven membranes (non-woven fabrics), microporous membranes, composite membranes, diaphragm paper, rolled membranes or spinning membranes. At least one of the isolating membrane of the present application may have a porous structure, and the size of the pore size is not particularly limited, as long as the purpose of the present application can be achieved. For example, the size of the pore size can be 0.01μm to 1μm. In the present application, the thickness of the isolating membrane is not particularly limited, as long as the purpose of the present application can be achieved. For example, the thickness can be 5μm to 500μm.
[0044] For example, the isolation membrane may include an isolation membrane substrate layer and a surface treatment layer. The isolation membrane substrate layer may be a non-woven fabric, a film or a composite film having a porous structure, and the material of the isolation membrane substrate layer may include but is not limited to at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the isolation membrane substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance.
[0045] The polymer layer contains polymers, and the material of the polymer may include but is not limited to at least one of vinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyimide, acrylonitrile-butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, acrylic acid-styrene copolymer, polydimethylsiloxane, sodium polyacrylate or carboxymethyl cellulose. The inorganic layer may include but is not limited to inorganic particles and inorganic layer binders. The present application has no particular restrictions on inorganic particles, for example, it may include but is not limited to at least one of ceramics, aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular limitation on the inorganic layer binder, for example, it may include but is not limited to at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.
[0046] The electrochemical device of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In some embodiments, the electrochemical device may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery, etc.
[0047] The preparation process of the electrochemical device is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0048] The second aspect of the present application provides an electronic device, comprising the electrochemical device in any embodiment of the present application. The electrochemical device provided by the present application has good rate performance and cycle performance, so that the electronic device provided by the present application has a long service life.
[0049] The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.
[0050] The present application provides an electrochemical device, which includes a positive electrode sheet, wherein the positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and in a scanning electron microscope photograph of a cross section of the positive electrode material layer, the cross-sectional area is greater than 5 μm 2 The radius of the minimum circumscribed circle of the contour of the positive electrode active material particle is R c , cross-sectional area greater than 5 μm 2 The radius of the maximum inscribed circle of the particle's contour is R i , satisfying 1<R c / R i The average value of is ≤3. The electrochemical device provided by the present application, wherein the positive electrode active material in the positive electrode material layer satisfies 1<R c / R i The average value is ≤3, which can effectively improve the lithium ion transmission efficiency of the positive electrode sheet, thereby improving the rate performance of the electrochemical device at room temperature and low temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the embodiments of the present application and the technical solutions of the prior art, the following briefly introduces the drawings required for use in the embodiments and the prior art. Obviously, the drawings described below are only some embodiments of the present application.
[0052] Figure 1 A scanning electron microscope photograph of a cross section of a positive electrode material layer in one embodiment of the present application;
[0053] Figure 2 It is a cross-sectional schematic diagram of a positive electrode plate in one embodiment of the present application.
[0054] Reference numerals: 10, positive electrode current collector, 20, positive electrode material layer, 21, positive electrode active material. DETAILED DESCRIPTION
[0055] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the accompanying drawings and examples. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field belong to the scope of protection of the present application.
[0056] Figure 1 A scanning electron microscope photograph of a cross section of a positive electrode material layer in an embodiment of the present application is shown. It can be seen from the figure that the size and shape of the particles of the positive electrode active material 21 are different. The minimum circumscribed circle of the outline of particle C is R1, and the maximum inscribed circle of the outline of particle C is R2; the minimum circumscribed circle of the outline of particle D is R3, and the maximum inscribed circle of the outline of particle D is R4. Among them, particle C is an example of the first particle in the present application, and particle D is an example of the second particle in the present application.
[0057] Figure 2 A schematic cross-sectional view of a positive electrode plate in an embodiment of the present application is shown. A positive electrode material layer 20 exists on both surfaces of the positive electrode current collector 10. The direction indicated by the arrow in the figure is the thickness direction of the positive electrode material layer 20. The cross-sectional view of the positive electrode material layer mentioned above in the present application refers to the cross-section obtained along the direction of the arrow in the figure.
[0058] It should be noted that, in the specific embodiment of the present application, the R c1 / R i1 The average value of the second particle R c2 / R i2 The average value can be controlled by controlling the ratio of the radius of the minimum circumscribed circle to the radius of the maximum inscribed circle of the raw material particles, as well as the Dv50 of the raw material, and comprehensively adjusting the stirring speed or calcination temperature during the preparation of the positive electrode active material.
[0059] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0060] Example
[0061] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0062] Test methods and equipment:
[0063] R i and R c Measurements:
[0064] At 25°C, the lithium-ion battery was charged to 4.2V at a constant current of 0.5C, then charged to 0.05C at a constant voltage of 4.2V, and then discharged to 2.8V at a constant current of 1C. The lithium-ion battery was disassembled, the positive electrode sheet was cleaned with DMC, and then dried at 60°C for 2h; the positive electrode sheet was cut along the thickness direction of the positive electrode sheet itself using an ion polisher to obtain a flat positive electrode sheet cross section; the cross section was tested using a scanning electron microscope (SEM); and the SEM image with a magnification of 1000 times was selected.
[0065] The software Image J was used to perform graphic morphology recognition on the above SEM images, and 100 cross sections that were completely within the image field of view and had a cross-sectional area greater than 5 μm were randomly selected. 2 The algorithm is used to calculate the radius R of the maximum inscribed circle of the particle. i and the radius R of the smallest circumscribed circle c Perform calculations (refer to "Kenneth C.Williams, Wei Chen, Sebastian Weeger, Timothy J.Donohue, Particle shape characterization and its application to discrete element modeling, Particuology, Volume 12, 2014, Pages 80-89, ISSN 1674-2001").
[0066] R c1 , R i1 , R c2 , R i2 The measurement method and R i and R c The same.
[0067] R c3 and R i3 The measurement is to prepare manganese dioxide into a slurry and then coat it on the substrate to form a film layer, and refer to R i and R c The solid content of the slurry (eg, 75 wt%) and the type of substrate are not particularly limited, as long as the purpose of the present application can be achieved. c4 and R i4 , R c5 and R i5 The measurement reference R c3 and R i3 measurement method.
[0068] Measurement of the area of the first and second particles and calculation of their area percentage:
[0069] The particle area was calculated using Image J software. c / R i The ratio determines whether the particle belongs to the first particle or the second particle, and the sum of particles with different belongings is recorded as the area of the first particle or the second particle. The area percentage of the first particle is the area of the first particle / image area×100%, and the area percentage of the second particle is the area of the second particle / image area×100%.
[0070] Measurement of positive electrode active material particle size:
[0071] The particle size of the positive electrode active material was measured using a Malvern particle size tester. The positive electrode active material was dispersed in ethanol, added to the Malvern particle size tester after ultrasonic treatment for 30 minutes, and the test was started. In the particle size distribution of the positive electrode active material on a volume basis, starting from the small particle size side, the particle size that reaches 10% of the volume accumulation is the Dv10 of the positive electrode active material, the particle size that reaches 50% of the volume accumulation is the Dv50 of the positive electrode active material, and the particle size that reaches 90% of the volume accumulation is the Dv90 of the positive electrode active material.
[0072] Test of element content:
[0073] According to the SEM image of the cross section of the positive electrode sheet obtained above, the second particles are determined according to the particle size and area in the image, and then an energy dispersive spectrometer (EDS) is used to test to determine the doping element and the element content;
[0074] The positive electrode material layer of the positive electrode sheet after washing with DMC is scraped off with a scraper, dissolved with a mixed solvent (for example, 0.4 g of positive electrode active material uses a mixed solvent of 10 ml of aqua regia (nitric acid and hydrochloric acid mixed in a volume ratio of 1:1) and 2 ml of HF), fixed to 100 mL, and then an inductively coupled plasma (ICP) analyzer is used to test the content of elements in the solution.
[0075] Positive electrode compaction density test:
[0076] At 25°C, the lithium-ion battery was charged to 4.2V at a constant current of 0.5C, then charged to 0.05C at a constant voltage of 4.2V, and then discharged to 2.8V at a constant current of 1C. The lithium-ion battery was disassembled, the positive electrode sheet was cleaned with DMC, and then dried at 60°C for 2h, and 5 positive electrode sheets of 5cm×5cm were cut. The thickness of the positive electrode sheets was measured by a micrometer, recorded as d0 cm; the positive electrode material layer in the positive electrode sheet was scraped off with a scraper, and the mass of the positive electrode material layer was weighed by a balance, recorded as mg. The thickness of the positive current collector after removing the positive electrode material layer was measured by a micrometer, recorded as d cm, and the compaction density of the positive electrode material layer was calculated according to the following formula:
[0077] Compacted density P = m / [25×(d0-d)], unit: g / cm 3 .
[0078] The compaction density of the positive electrode material layer is the average value of the compaction density of the positive electrode material layer in the five positive electrode sheets cut as above.
[0079] Particle size test in the positive electrode material layer:
[0080] At 25°C, the lithium-ion battery was charged to 4.2V at a constant current of 0.5C, then charged to 0.05C at a constant voltage of 4.2V, and then discharged to 2.8V at a constant current of 1C. The lithium-ion battery was disassembled, and the disassembled positive or negative electrode pieces were sintered into powder at 400°C in a vacuum, and the particle size was tested using a particle size analyzer to obtain the values of Dv10, Dv50, and Dv90.
[0081] Among them, Dv90 refers to the particle size that reaches 90% of the volume accumulation from the small particle size side in the volume-based particle size distribution, Dv50 refers to the particle size that reaches 50% of the volume accumulation from the small particle size side in the volume-based particle size distribution, and Dv10 refers to the particle size that reaches 10% of the volume accumulation from the small particle size side in the volume-based particle size distribution.
[0082] Tests of rate performance and 25°C cycle performance:
[0083] (1) 25℃2C room temperature rate performance and 25℃ cycle performance
[0084] At 25°C, the lithium-ion battery is charged to 4.2V at a constant current of 0.5C, then charged to 0.05C at a constant voltage of 4.2V, and then discharged to 2.8V at a constant current of 0.2C. The discharge capacity is recorded as D 01 ; Charge the lithium-ion battery to 4.2V at 0.5C constant current, then charge to 0.05C at 4.2V constant voltage, and then discharge to 2.8V at 2C constant current. Record the discharge capacity as D1. 25℃ 2C rate retention rate (%) = D1 / D 01 ×100%.
[0085] According to the above steps, the lithium-ion battery is subjected to multiple cycles of "0.5C charge-2C discharge" for 1000 cycles. The discharge capacity after the 1000th cycle is D 10 . Capacity retention rate after 1000 cycles at 25°C (%) = D 10 / D 01 ×100%.
[0086] (2) -10℃ 1C low temperature rate performance
[0087] At 25°C, the lithium-ion battery is charged to 4.2V at a constant current of 0.5C, then charged to 0.05C at a constant voltage of 4.2V, and then discharged to 2.8V at a constant current of 1C. The discharge capacity is recorded as D 02 ; At 25℃, charge the lithium-ion battery to 4.2V at 0.5C constant current, then charge to 0.05C at 4.2V constant voltage, adjust the temperature to -10℃, leave the battery for 30min, then discharge to 2.8V at 1C constant current, record the discharge capacity as D2. -10℃1C rate retention (%) = D2 / D 02 ×100%.
[0088] Cycle performance test:
[0089] 40℃ 500 cycles capacity retention rate:
[0090] The lithium-ion battery is charged at 40°C at a constant current of 0.5C to 4.2V, then charged at a constant voltage to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 1C to 2.8V. This is one charge and discharge cycle, and the discharge capacity is recorded as D 03 ; According to the above steps, the lithium-ion battery was cycled 500 times, and the discharge capacity after the 500th cycle was tested as D3. The capacity retention rate after 500 cycles at 40°C (%) = D3 / D 03 ×100%.
[0091] Test of manganese content in negative electrode:
[0092] The lithium-ion battery in a fully discharged state after 500 cycles at 40°C was disassembled, the negative electrode plate was cleaned with DMC, and then dried at 60°C for 2 hours, the negative electrode material layer of the negative electrode plate was scraped off with a scraper, and dissolved with a mixed solvent (for example, 0.4g of negative electrode active material uses 10ml of aqua regia (nitric acid and hydrochloric acid mixed in a volume ratio of 1:1)), the volume was fixed to 100ml, and then the manganese content in the solution was tested using an ICP analyzer.
[0093] Example 1-1
[0094] <Preparation of positive electrode sheet>
[0095] Weigh 203.3 kg of lithium carbonate (including 18.71% lithium by mass), R c3 / R i31000kg of manganese dioxide (of which the mass percentage of Mn element is 60.22%) with an average value of 2.9 and Dv50 of 17.2μm and 56.2kg of aluminum oxide (Al2O3, with a mass percentage of aluminum element of 52.91%) containing M2 metal element are mixed in a high-speed mixer at a speed of 300r / min for 20min to obtain a mixture, which is placed in an air kiln and heated to 790℃ at 5℃ / min for 24h, taken out after natural cooling, and passed through a 300-mesh sieve to obtain a manganese-containing composite metal oxide, namely LMO. Among them, R c3 R is the radius of the minimum circumscribed circle of the manganese dioxide particle. i3 is the radius of the largest inscribed circle of the contour of the manganese dioxide particle.
[0096] The positive electrode active material LMO, the conductive agent Super P, and the binder polyvinylidene fluoride are mixed in a mass ratio of 96:2.4:1.6, and N-methylpyrrolidone (NMP) is added. The system is stirred under the action of a vacuum mixer until it becomes uniform to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and the aluminum foil is dried at 85°C to obtain a positive electrode sheet with a coating thickness of 110μm and a single-sided positive electrode material layer. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer. Then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 85°C for 4h to obtain a positive electrode sheet with a specification of 74mm×867mm. Among them, the R of the positive electrode active material c / R i The average value is 2.9 and Dv50 is 17.9μm.
[0097] <Preparation of negative electrode sheet>
[0098] The negative electrode active material artificial graphite, the conductive agent Super P, the thickener sodium carboxymethyl cellulose (CMC), and the binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 96.4:1.5:0.5:1.6, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry is 70wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and the copper foil is dried at 85°C to obtain a negative electrode sheet with a coating thickness of 130μm and a negative electrode material layer coated on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. Then, after cold pressing, cutting, and slitting, it is dried under vacuum conditions at 120°C for 12h to obtain a negative electrode sheet with a specification of 79mm×972mm.
[0099] <Preparation of Electrolyte>
[0100] In an argon atmosphere glove box with a water content of <10ppm, linear carbonate DEC and cyclic carbonate EC were mixed in a mass ratio of 57.5:30 to obtain a base solvent, and then lithium salt LiPF6 was added to the base solvent to dissolve and mix evenly. Among them, based on the mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, and the rest is the base solvent.
[0101] <Preparation of Separator Film>
[0102] Mix water-based polyvinylidene fluoride, aluminum oxide, and polypropylene in a mass ratio of 1:8:1, add to deionized water, and stir to obtain a coating slurry with a solid content of 50wt%. The coating slurry is evenly coated on one surface of a PE film (provided by Celgard) with a thickness of 5μm, and dried at 85°C to obtain a single-sided coated isolation membrane with a coating thickness of 5μm. Repeat the above steps on the other surface of the isolation membrane to obtain a double-sided coated isolation membrane. Then, after drying and cold pressing, an isolation membrane is obtained. Among them, the porosity of the isolation membrane is 39%.
[0103] <Preparation of lithium-ion batteries>
[0104] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and after drying, the electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, degassing, trimming, and other processes. Among them, the formation conditions are to charge to 3.3V at a constant current of 0.02C, and then to 3.6V at a constant current of 0.1C.
[0105] Example 1-2 to Example 1-4
[0106] In addition to adjusting the R c3 / R i3 The average value and Dv50 of the positive electrode active material R c / R i Except that the average values and Dv50 are as shown in Table 1, the rest are the same as Example 1-1.
[0107] Example 1-5 and Example 1-6
[0108] In addition to replacing manganese dioxide in the raw material with manganese tetraoxide when preparing LMO, and adjusting the R c4 / R i4 The average value and Dv50 of the positive electrode active material R c / R iExcept that the average values and Dv50 are shown in Table 1, the rest are the same as those in Example 1-1. c4 R is the radius of the minimum circumscribed circle of the contour of the manganese oxide particle. i4 is the radius of the largest inscribed circle of the contour of the manganese manganese tetroxide particle.
[0109] Example 2-1
[0110] In addition to the use of positive electrode active materials LMO and positive electrode active materials LiNi in <Preparation of positive electrode sheet> 0.55 Co 0.15 Mn 0.3 O2 (NCM5515), conductive agent Super P, and binder polyvinylidene fluoride were mixed in a mass ratio of 76.8:19.2:2.4:1.6, NMP was added, and the system was stirred in a vacuum mixer until it became uniform to obtain a positive electrode slurry with a solid content of 75wt%, and the R of manganese dioxide was adjusted. c3 / R i3 The average value and Dv50 of the second particle R c / R i Except that the average values of and Dv50 of the positive electrode active material are shown in Table 2, the rest are the same as Example 1-1.
[0111] The NCM5515 is prepared by the following method: lithium carbonate (wherein the lithium content is 18.71% by weight) and R c5 / R i5 The average value is 1.2, and the Dv50 is 16.3μm. 0.55 Co 0.15 Mn 0.3 The (OH)2 precursor is mixed in a high-speed mixer at a speed of 300r / min for 20min according to the ratio of the molar number of Li to the molar number of transition metal elements (the sum of the molar numbers of Ni, Co and Mn) of 1.05:0.997 to obtain a mixture, which is placed in an oxygen kiln and heated to 890℃ at 5℃ / min for 12h. After natural cooling, it is taken out and passed through a 300-mesh sieve to obtain lithium nickel cobalt manganese oxide, namely NCM5515. Among them, R c5 For you 0.55 Co 0.15 Mn 0.3 The radius of the minimum circumscribed circle of the (OH)2 precursor particle, R i5 For you 0.55 Co 0.15 Mn 0.3 The radius of the largest inscribed circle of the contour of the (OH)2 precursor particle.
[0112] Embodiment 2-2 to Embodiment 2-4, Embodiment 2-7
[0113] In addition to mixing the corresponding positive electrode active materials according to Table 2, adjusting the R c3 / R i3 The average value and Dv50, and / or Ni 0.55 Co 0.15 Mn 0.3 R of (OH)2 precursor c5 / R i5 The average value and Dv50 of R c1 / R i1 The average value, R c2 / R i2 The average value of the first particle area percentage, the second particle area percentage, the Dv50 of the positive electrode active material and the particle size distribution (Dv90-Dv10) / Dv50 of the positive electrode active material are shown in Table 2, and the rest is the same as Example 2-1. Among them, NCM6010 in Table 2 is LiNi 0.6 Co 0.1 Mn 0.3 O2, NCM8309 for LiNi 0.83 Co 0.09 Mn 0.08 O2; by adjusting the ratio of the molar number of Li to the molar number of the transition metal element when preparing NCM5515, NCM6010 and NCM8309 satisfy the above chemical formula.
[0114] Example 2-5 and Example 2-6
[0115] In addition to replacing manganese dioxide in the raw material with manganese tetraoxide when preparing the first particle of LMO, and adjusting the R c4 / R i4 The average value and Dv50 of manganese dioxide are adjusted when preparing the second particle LMO. c3 / R i3 The average value and Dv50 of R c1 / R i1 The average value, R c2 / R i2 The average values, area percentage of the first particles, area percentage of the second particles, Dv50 of the positive electrode active material and the particle size distribution (Dv90-Dv10) / Dv50 of the positive electrode active material are shown in Table 2, and the rest are the same as Example 2-1.
[0116] Example 3-1 to Example 3-7
[0117] Except for adjusting the types and contents of the linear carbonate and the cyclic carbonate according to Table 3 to obtain the base solvent, the rest is the same as Example 2-1.
[0118] Example 4-1 to Example 4-9
[0119] Except that in <Preparation of Electrolyte>, a sulfonate compound is further added to the electrolyte, and the type and mass percentage of the sulfonate compound are adjusted according to Table 4, the rest is the same as Example 2-1.
[0120] Example 5-1 to Example 5-6
[0121] Except that a compound containing the metal element M2 is added according to Table 5 during the preparation of LMO and its content is adjusted so that the mass percentage of the metal element M2 is as shown in Table 5, the rest is the same as Example 2-1.
[0122] Embodiment 5-7
[0123] Except for using commercial LiFePO4 (denoted as LFP) with a Dv50 of 1.0 μm to replace NCM5515, the rest is the same as Example 5-3.
[0124] Embodiment 5-8
[0125] In addition to using commercial LiMn with a Dv50 of 1.0 μm 0.75 Fe 0.25 Except that PO4 (denoted as LMFP) replaces NCM5515, the rest is the same as Example 5-3.
[0126] Embodiment 5-9
[0127] The method is the same as Example 5-3 except that commercial LFP with a Dv50 of 1.0 μm is used to replace part of NCM5515 so that the mass ratio of LMO, NCM5515, LFP, Super P and polyvinylidene fluoride is 76.8:9.2:10:2.4:1.6.
[0128] Comparative Example 1
[0129] In addition to R c / R i Except that the average values of and Dv50 of the positive electrode active material are shown in Table 1, the rest are the same as Example 1-1.
[0130] The preparation parameters and performance tests of various embodiments and comparative examples are shown in Tables 1 to 5.
[0131] Table 1
[0132]
[0133]
[0134] It can be seen from Examples 1-1 to 1-6 and Comparative Example 1 that when R c / R i The value of is within the scope of the present application, and the obtained lithium ion battery has both good low-temperature rate performance and normal-temperature rate performance.
[0135] Table 2
[0136]
[0137] The area percentage of the first particles, the area percentage of the second particles, the Dv50 of the positive electrode active material and the value of (Dv90-Dv10) / Dv50 usually affect the performance of the lithium-ion battery. It can be seen from Examples 2-1 to 2-7 that when the area percentage of the first particles, the area percentage of the second particles, the Dv50 of the positive electrode active material and the value of (Dv90-Dv10) / Dv50 are within the range of the present application, the obtained lithium-ion battery has good low-temperature rate performance and normal-temperature rate performance.
[0138] Table 3
[0139]
[0140]
[0141] The type and mass percentage of chain carbonates and cyclic carbonates in the electrolyte, as well as the value of ω1 / ω2 usually affect the performance of lithium-ion batteries. It can be seen from Examples 2-1 and 3-1 to 3-7 that when the type and mass percentage of chain carbonates and cyclic carbonates, as well as the value of ω1 / ω2 are within the range of the present application, the obtained lithium-ion battery has good low-temperature rate performance.
[0142] Table 4
[0143]
[0144] Note: “ / ” in Table 4 indicates that there is no corresponding preparation parameter or substance.
[0145] It can be seen from Examples 2-1 and 4-1 to 4-9 that the addition of sulfonate compounds to the electrolyte can improve the cycle performance of lithium-ion batteries at high temperatures and the dissolution of manganese on the negative electrode sheet. It can be seen from Examples 4-1 to 4-9 that when the type and mass percentage of the sulfonate compounds are within the scope of this application, the obtained lithium-ion battery has good high-temperature cycle performance and less manganese dissolution on the negative electrode sheet. And, when the value of A / B is within the scope of this application, the obtained lithium-ion battery has good high-temperature cycle performance and less manganese dissolution on the negative electrode sheet.
[0146] Table 5
[0147]
[0148] The type of elements in the positive electrode active material usually affects the performance of the lithium-ion battery. It can be seen from Examples 2-1, 5-1 to 5-9 that when the positive electrode active material includes Mn and the metal element M1, the obtained lithium-ion battery has good low-temperature rate performance. In addition, it can be seen that when the second particle contains the metal element M2 and its type and mass percentage are within the scope of the present application, the obtained lithium-ion battery has good low-temperature rate performance.
[0149] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrochemical device comprising a positive electrode sheet, the positive electrode sheet comprising a positive electrode material layer, the positive electrode material layer comprising a positive electrode active material, and in a scanning electron microscope photograph of a cross section of the positive electrode material layer, an area greater than 5 μm 2 The radius of the minimum circumscribed circle of the contour of the positive electrode active material particle is R c , area larger than 5μm 2 The radius of the maximum inscribed circle of the contour of the positive electrode active material particle is R i , satisfying 1<R c / R i The average value of is ≤3; among them, The area is larger than 5 μm 2 The positive electrode active material particles include a first particle and a second particle, the radius of the minimum circumscribed circle of the outline of the first particle is R c1 , the radius of the maximum inscribed circle of the outline of the first particle is R i1 , satisfying 1<R c1 / R i1 The average value of is ≤1.5; the radius of the minimum circumscribed circle of the contour of the second particle is R c2 , the radius of the maximum inscribed circle of the contour of the second particle is R i2 , satisfying 1.5<R c2 / R i2 The average value is ≤3.
2. The electrochemical device according to claim 1, which satisfies: Based on the cross-sectional area of the positive electrode material layer, the area percentage of the first particles is greater than 0% and less than or equal to 50%, and the area percentage B of the second particles is 30% to 80%; and / or, The average cross-sectional area of the first particles is smaller than the average cross-sectional area of the second particles.
3. The electrochemical device according to claim 1 further comprises an electrolyte, wherein the electrolyte comprises a linear carbonate and a cyclic carbonate, wherein the mass percentage of the linear carbonate is ω1, and the mass percentage of the cyclic carbonate is ω2, based on the mass of the electrolyte, and ω1 / ω2 is 0.75 to 2.
5.
4. The electrochemical device according to claim 1, wherein Satisfy at least one of conditions (a) to (b): (a) the positive electrode active material comprises lithium manganate; (b) The positive electrode active material includes a composite metal oxide of lithium element and a transition metal element, the transition metal element includes Mn and a metal element M1, and the metal element M1 includes at least one of Ni, Co or Fe.
5. The electrochemical device according to claim 1, wherein The second particles include a metal element M2, and the metal element M2 includes at least one of Al, Mg, or Nb.
6. The electrochemical device according to claim 1, wherein The second particles include a metal element M2, and based on the mass of the second particles, the mass percentage of the metal element M2 is 0.1% to 3%.
7. The electrochemical device according to claim 1, wherein the volume particle size distribution of the positive electrode active material satisfies at least one of the conditions (c) to (d): (c) 9μm≤Dv50≤22μm; (d)0.9≤(Dv90-Dv10) / Dv50≤2.
8. The electrochemical device according to claim 3, wherein: The linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl propyl carbonate, dipropyl carbonate, methyl isopropyl carbonate, methyl butyl carbonate or dibutyl carbonate.
9. The electrochemical device according to claim 3, wherein: The cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate or butylene carbonate.
10. The electrochemical device according to claim 2, further comprising an electrolyte, wherein the electrolyte comprises a sulfonate compound, and the mass percentage of the sulfonate compound based on the mass of the electrolyte is A, satisfying 0.006≤A / B≤0.
1.
11. The electrochemical device according to claim 10, wherein: 0.5%≤A≤10%。 12. The electrochemical device according to claim 10, wherein: The sulfonate compound includes at least one of the following structural compounds I-1 to I-14:
13. The electrochemical device according to claim 1, further comprising a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode material layer, wherein the negative electrode material layer comprises a negative electrode active material, and wherein the negative electrode active material comprises at least one of artificial graphite, natural graphite or hard carbon.
14. An electronic device comprising the electrochemical device according to any one of claims 1 to 13.
Citation Information
Patent Citations
Secondary battery
CN110447129A